2014
DOI: 10.1080/13102818.2014.947066
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial potential of streptomycete strains from Antarctic soils

Abstract: The exploration of habitats with unusual environment and poorly explored areas such as Antarctica is one of the strategies for discovery of new biologically active substances and/or new producers. The aim of this study was to identify the actinomycetes isolated from the soils of the island Livingston – Antarctica and to investigate their potential to synthesize antibacterial agents against phytopathogens. Twenty-three actinomycete strains were the object of this study. Using PCR (polymerase chain reaction) amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 9 publications
1
19
0
2
Order By: Relevance
“…Antarctic Streptomyces spp. with broadspectrum antibacterial activity against both Grampositive and Gram-negative bacteria were previously reported by Encheva-Malinova et al (2014). The inhibition assay was performed on different foodborne pathogenic bacteria and may not reflect the actual bacterial community in the Antarctic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Antarctic Streptomyces spp. with broadspectrum antibacterial activity against both Grampositive and Gram-negative bacteria were previously reported by Encheva-Malinova et al (2014). The inhibition assay was performed on different foodborne pathogenic bacteria and may not reflect the actual bacterial community in the Antarctic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Streptomyces bacteria happen to be widely distributed in extreme and underexplored environments such as deserts [70] , caves [71] , hot springs [72] , mangroves [33,73] , mountain plantations [55] , Arctic and Antarctic regions [74,75] . These environments are often characterized by certain fluctuations in environmental conditions, extreme high/low temperature, acidic/alkaline pH, limitation of nutrients, or high radiation [1] .…”
Section: Other Unique Environmentsmentioning
confidence: 99%
“…While the majority of actinomycetes studied to date are found in terrestrial environments, these organisms have been identified in a wide range of extreme environments and marine locations. These bacteria occupy environments where the soil has a high salt concentration such as the Great Salt Plains of Oklahoma, Antarctica, and several marine locations (Hotta et al, 1980 ; Lam, 2006 ; Encheva-Malinova et al, 2014 ; Gad, 2014 ). Another variation seen in the growth pattern of actinomycetes is in the wide range of temperatures where they occur.…”
Section: Introductionmentioning
confidence: 99%